(Un)Equal Pathways to Higher Education Social Origins and Destinations of Colombian Graduates - Cuenca Hernández, Andrea (Sozialisations- und Bildungsforschung: international, komparativ, historisch Research in Socialisation and Education: international, comparative, historical, 2021)
Inequality of educational opportunities (IEO) is a recurring topic in both public debate and academic research. This book contributes to the contemporary discussion on IEO with a focus on individual trajectories over the life course. It provides empirical evidence on the magnitude and the mechanisms of IEO in Colombia, a country with extreme, persistent levels of social inequality. Using national administrative databases, the author examines the effect of social origin on academic and labor market outcomes among university graduates. Drawing on a comprehensive theoretical approach to stratification and higher education, this volume discusses how the interaction between family background and segmentation of educational institutions might influence individuals' outcomes. As such, it will appeal to scholars, policy makers, and practitioners with interests in education, social inequality, social policy, higher education research, and international/comparative education.